Twin reverse arterial perfusion (TRAP) sequence in monochorionic twin pregnancy with acardiac fetus - Sáenz, Igor Hermann Huerta (2013)
Twin reverse arterial perfusion (TRAP) sequence is a pathology associated to monochorionic twin pregnancy complications that may show amniotic fluid volume discordance between fetuses and even coexistence of one acardiac fetus and one healthy fetus. A TRAP case diagnosed in the second trimester of pregnancy is reported and treatment and perinatal results are discussed. Keywords: Acardiac fetus, twin reverse arterial perfusion, TRAP sequence, monochorionic twin pregnancy.